In vivo RNAi screen and validation reveals Ngp, Hba-a1, and S100a8 as novel inhibitory targets on T lymphocytes in liver cancer - Hochnadel, Inga; Hoenicke, Lisa; Petriv, Nataliia; Suo, Huizhen; Groebe, Lothar; Olijnik, Chantal; Bondarenko, Nina; Alfonso, Juan C.; Jarek, Michael; Shi, Ruibing; Jeron, Andreas; Timrott, Kai; et al. (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) represents the third deadliest cancer worldwide with limited treatment options. Immune checkpoint inhibitors (ICIs) have revolutionized HCC therapy, but immune suppression within the tumor microenvironment remains a major challenge. Therefore, in this study, we aimed to define novel ICI molecules arising on T cells during aggressive HCC development.MethodsUsing autochthonous HCC models, we performed microarray analyses followed by in vivo RNA interference screen and identified several new ICI molecules on CD4 and CD8 T lymphocytes in HCC-bearing mice. Short hairpin RNA (shRNA)-mediated knockdown of the ICI molecules was performed to validate their functional role in T cell activity and survival of HCC-bearing mice. Finally, we searched for the presence of the defined ICI molecules in HCC patients.ResultsWe identified neutrophilic granule protein (Ngp), hemoglobin subunit alpha-1 (Hba-a1), and S100 calcium-binding protein a8 (S100a8) as novel inhibitory molecules of T cells in HCC. The specific shRNA-based knockdown of these inhibitory targets was safe, led to a downregulation of classical ICI molecules (PD-1, PD-L1, 4-1BBL, CD160), and kept liver parameters under control in murine HCC. Besides, we detected upregulation of S100A8 and S100A9 in blood and liver tissues in HCC patients, supporting their clinical relevance.ConclusionThe obtained results pave the way for the use of the newly defined ICI molecules Ngp, Hba-a1, and S100a8 as novel immunotherapeutic targets in further preclinical and clinical studies in HCC patients.